FORMULASI DAN UJI STABILITAS FISIK DEODORAN SPRAY KOMBINASI EKSTRAK DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav.) DAN DAUN BELIMBING WULUH (Averrhoa bilimbi L) SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus aureus - Anisa Nurjanah; Zaenal Fanani; Fahrudin Arif (Nusantara Hasana Journal, 2025)
Body odor problems triggered by the activity of bacteria such as Staphylococcus aureus are a concern in tropical regions such as Indonesia, which have high temperatures and humidity. Long-term use of synthetic chemical deodorants carries the risk of side effects, so safe and effective natural alternatives are needed. This study aims to formulate and evaluate the physical stability and antibacterial effectiveness of a spray deodorant preparation made from a combination of red betel leaf extract (Piper crocatum Ruiz and Pav.) and starfruit leaf extract (Averrhoa bilimbi L.). The extract was obtained through a maceration method with 70% ethanol as a solvent. This study used a laboratory experimental design with a quantitative approach. The study population was a spray deodorant preparation formulated in four variations: F0 (Negative control), F1 (7.5% red betel leaf + 2.5% starfruit leaf), F2 (5% + 5%), and F3 (2.5% + 7.5%). Physical stability tests included organoleptic tests, pH, displaced volume, and homogeneity. Antibacterial activity test was carried out using the well diffusion method against Staphylococcus aureus ATCC 25923. Data analysis was performed using normality test, homogeneity test, and one-way ANOVA test, and Tukey HSD post-hoc test. The results showed significant differences between treatment groups, but no significant differences between test formulas. All formulas met physical stability standards and showed strong antibacterial activity (inhibition zone 12.1 -14.37 mm). Formula F2 showed the highest inhibition, indicating a synergistic effect of a balanced extract ratio. This study contributes to the development of natural spray deodorant products that are safe, effective, and have the potential to replace synthetic ingredients in pharmaceutical formulations.